(untitled) (West Sussex, 2016)
Contains the latest research advances in computational nanomechanics in one comprehensive volume: Covers computational tools used to simulate and analyse nanostructures, Includes contributions from leading researchers, Covers of new methodologies/tools applied to computational nanomechanics whilst also giving readers the new findings on carbon-based aggregates (graphene, carbon-nanotubes, nanocomposites), Evaluates the impact of nanoscale phenomena in materials
Keywords: Hệ thống cơ điện nano,Nanotechnology,Nanoelectromechanical systems,Công nghệ nanô; Mô hình toán học,Mathematics,Mathematical models,Toán học